ELASTIC BALANCE OF HALF-PLANE WITH RECTILINEAR SOMILIAN DISLOCATION - Valentin Y. Molotnikov; Antonina A. Molotnikova, (Advanced Engineering Research, 2011)
Closed solution of the elasticity problem on the half-plane balance with rectilinear shift dislocation is presented. The dislocation core is assumed to lie inside the area, and the slip line - to cross the half-plane boundary. The solution applicability to the estimation of the crust stress state near disjoint dislocations is considered.